Avaliações e correlações das propriedades reológicas, mecânicas e de cinética de cristalização de polímeros utilizados em processo de impressão 3d por FFF - Sanchez, Larissa Cristina (Universidade Federal de São Carlos, 2018)
Recently there has been an interest increase in the additive manufacturing process (AM), Fused Filament Fabrication (FFF) is one of the most commercially important extrusion-based process. The success of this technology depends on the correct choice of materials and process parameters used. This master's project aimed at modeling the process in order to understand the behavior under flow of the polymer during 3D printing. The rheological and morphological characteristics of the materials were correlated to the mechanical and surface finishing properties of the pieces. In a first step, a commercial grade of natural ABS and PLA filaments were evaluated. In the second stage, a natural PLA and a white pigmented PLA were evaluated for crystallization kinetics. In addition, the process variables were determined according to a central composite statistical design, with the independent variables (printing temperature and process speed) and responses (percentage of crystallinity and flexural mechanical properties). The results revealed that the typical shear rates of the process are between 800 and 1,600 s-1 and for this range the behavior of the polymer can be described by the Power Law. It was obtained that the FFF process is sensitive to shear rate variation, and materials with higher elasticity and faster crystallization kinetics tend to have better surface quality of the form. The study of the crystallization kinetics of PLA showed that, although the pigment of the white coloring material does not interfere in the rheological properties of the material, it alters the crystallization kinetics of the matrix, increasing the crystallinity potential.
Evaluations and correlations of reological, mechanical properties and crystallization kinetics of polymers used in 3d printing process by FFF
Keywords: Impressão 3D; Manufatura aditiva; Reologia; Cristalização; FFF; 3D printing; Additive manufacturing; Rheology; Crystallization; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS